Growth Morphologies, Fragmentation Patterns, and Hardness in Sodium Hydrogen Urate Monohydrate. Issue 1721 (30th January 2015) - Brune, A. B.; Petuskey, W.T.
ABSTRACT: Mechanical properties and new morphological data on synthetic sodium hydrogen urate monohydrate are reported and interpreted. Crystals formed in supersaturated aqueous solutions were identified by powder x-ray diffraction. Intact grains and separate needles were examined by several microscopy techniques, some reported here for the first time. The dominant morphology was spherulite-type, comprising tapered, branched blades (needles) radiating out of a common core. The pointed blade tips were truncated by (011) planes, corresponding to hydrogen-bonded planes. Branching was at about a 5° angle or its multiples, suggesting it accommodated by dislocation arrays at the low angle boundaries, as is often seen in twinning. Vicker's micro-hardness, extrapolated to zero porosity, was 0.90 GPa, which is greater than the hardness measured by nano-indentation. Present results are anticipated to be useful in interpreting the mechanical characteristics of the material crystallized in vivo and its action concerning gout, and affording inferences on the role of the milieu on morphologies, fragmentation, and hardness.